Evaluation of the effects of cotton roll-biting on debonding pain: a split-mouth study - Celebi, Fatih (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Introduction: Debonding pain is an unpleasant sensation that is frequently encountered during debonding procedure. Aim of the study: To investigate the effectiveness of cotton roll-biting on pain caused by the debonding procedure. Materials and methods: 102 patients (61 females, 41 males) who were at the debonding stage in orthodontic treatment were included in the research. The study was planned using a split-mouth design: one side of the jaw was the study, and the other side was the control. The anxiety level of participants was measured before debonding. On the study side, debonding was performed while patients were biting a cotton roll. On the control side, debonding was implemented as a routine debonding procedure. Study and control sides were assigned differently in each successive patient. The debonding pain of each tooth was recorded using the Visual Analog Scale prepared separately for each tooth. Shapiro–Wilk and Mann–Whitney U tests were used for statistical analysis. For both gender groups, patients were sequenced according to the average amount of pain per tooth. Subsequently, statistical analysis was repeated by using 50% of patients suffering more pain. Results: In the lower second premolar tooth, a statistically significant difference was detected. Pain scores were statistically higher in the study side for this tooth. No statistically significant differences were found for all other teeth. Conclusions: Cotton roll-biting has no alleviating effect on debonding pain. When debonding is performed gently using a squeezing action without applying torsional forces, additional pain relief methods are not required.